Immobilisation of lead (Pb) using ladle furnace slag and CO2 - Goh, Yu Ting (Nanyang Technological University, 2021)
Lead (Pb) is a naturally occurring heavy metal found in the environment and is known for its adverse impact on mankind. Ladle furnace slag (LFS) is a by-product from the steelmaking industry that has always been landfilled but is currently garnering interest for its potential applications as a construction material in civil engineering. However, limited studies have been conducted on using LFS to immobilise heavy metals. In this context, this study aims to investigate the use of LFS to immobilise lead (Pb) by curing and carbonation. The properties of LFS were studied through laboratory tests, including carbonation, leaching test, X-ray diffraction (XRD), and Field Emission Scanning Electron Microscope (FESEM) tests. Overall, it was found that curing did not have much effect on reducing the leaching of Pb from the LFS sample while LFS + CO2 delivered promising results in reducing the leaching of Pb. The 28-day LFS sample with an initial concentration of 25000 mg/kg of Pb was found to have ettringite, which can absorb heavy metals. The presence of ettringite was confirmed by the SEM images. For LFS samples that underwent carbonation, it is observed that the maximum CO2 uptake takes place within the first 8 hours of carbonation. The 128-hour carbonated sample with an initial concentration of 25000 mg/kg of Pb has the lowest pH levels and falls within the range of pH where Pb has the lowest solubility. The XRD results and SEM images of carbonated LFS samples confirm the presence of calcite and lead carbonate.